Lower Face: Clinical Anatomy and Regional Approaches with Injectable Fillers. (November 2015) - Braz, André; Humphrey, Shannon; Weinkle, Susan; Yee, G. Jackie; Remington, B. Kent; Lorenc, Z. Paul; Yoelin, Steve; Waldorf, Heidi A.; Azizzadeh, Babak; Butterwick, Kimberly J.; de Maio, Mauricio; Sadick, Neil; et al.
Abstract : Supplemental Digital Content is available in the text.